The Factors Triggering Nanisca to Forbid the Members of Agojie to Have Families in The Woman King Film - Sri Marleni; Sahril Mujani; Lisna Farida Sitohang (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
This study investigates the factors leading Nanisca, the main character in The Woman King movie, to prohibit Agojie members from forming families. The researchers employ Feminism and Postcolonialism theories, focusing on radical feminism to identify Nanisca's motivations. Additionally, Oppression theory is utilized to depict the oppression experienced by Agojie members and other citizens of Dahomey, Mahi, and small kingdoms. The qualitative approach, along with observation and library research, is employed for this study. The findings reveal two main factors behind Nanisca's prohibition: Agojie members' negative experiences with women trafficking, sexual abuse, and verbal/non-verbal oppression. To combat these issues, Nanisca employs radical feminist strategies and enforces a rule against warriors having families, symbolizing her resistance against patriarchal oppression